Successes in African agriculture: results of an expert survey - Gabre-Madhin, Eleni Zaude; Haggblade, Steven (International Food Policy Research Institute, 2003)
Using primary data from a survey of expert opinion, this paper identifies key successes emerging in African agriculture. Among these, major commodity-specific successes identified include breakthroughs in maize breeding across Africa, sustained gains in cassava breeding and successful combat of its disease and pests, control of the rinderpest livestock disease, booming horticultural and flower exports in East and Southern Africa and increased cotton production and exports in West Africa. Using a dynamic analytical framework, the paper attempts to identify key ingredients that appear necessary for building on these individual cases and expanding them into broad-based agricultural growth.